Bioengineering of CuO porous (nano)particles: role of surface amination in biological, antibacterial, and photocatalytic activity - Bagherzadeh, Mojtaba; Safarkhani, Moein; Ghadiri, Amir Mohammad; Kiani, Mahsa; Fatahi, Yousef; Taghavimandi, Fahimeh; Daneshgar, Hossein; Abbariki, Nikzad; Makvandi, Pooyan; Varma, Rajender S; Rabiee, Navid (Scientific reports, 2022)
Nanotechnology is one of the most impressive sciences in the twenty-first century. Not surprisingly, nanoparticles/nanomaterials have been widely deployed given their multifunctional attributes and ease of preparation via environmentally friendly, cost-effective, and simple methods. Although there are assorted optimized preparative methods for synthesizing the nanoparticles, the main challenge is to find a comprehensive method that has multifaceted properties. The goal of this study has been to synthesize aminated (nano)particles via the Rosmarinus officinalis leaf extract-mediated copper oxide; this modification leads to the preparation of (nano)particles with promising biological and photocatalytic applications. The synthesized NPs have been fully characterized, and biological activity was evaluated in antibacterial assessment against Bacillus cereus as a model Gram-positive and Pseudomonas aeruginosa as a model Gram-negative bacterium. The bio-synthesized copper oxide (nano)particles were screened by MTT assay by applying the HEK-293 cell line. The aminated (nano)particles have shown lower cytotoxicity (~ 21%), higher (~ 50%) antibacterial activity, and a considerable increase in zeta potential value (~ + 13.4 mV). The prepared (nano)particles also revealed considerable photocatalytic activity compared to other studies wherein the dye degradation process attained 97.4% promising efficiency in only 80 min and just 7% degradation after 80 min under dark conditions. The biosynthesized copper oxide (CuO) (nano)particle's biomedical investigation underscores an eco-friendly synthesis of (nano)particles, their noticeable stability in the green reaction media, and impressive biological activity.
Keywords: HEK293 Cells; Metal Nanoparticles; Porosity; oxidy; měď; HEK293 buňky; poréznost; Anti-Bacterial Agents; Humans; Bioengineering; aminace; Oxides; Copper; kovové nanočástice; Amination; lidé; antibakteriální látky; bioinženýrství